Influence of structure phase transition on the thermoelectric properties of Cu2Se1−xTex liquid-like compounds. Issue 40 (15th September 2022) - Mac, Trung Kien; Ta, Thi Thu; Nguyen, Huu Tuan; Nguyen, Van Du; Pham, Thi Lan Huong; Duong, Van Thiet; Thanh, Tran Dang; Phan, Bach Thang; Duong, Anh Tuan
Abstract : Copper chalcogenide Cu2 (Se, Te) compounds are well known as typical p-type thermoelectric materials with a figure of merit ( ZT ) that can be optimized by the ratio of Se : Te. Abstract : Copper chalcogenide Cu2 (Se, Te) compounds are well known as typical p-type thermoelectric materials with a figure of merit ( ZT ) that can be optimized by the ratio of Se : Te. Here, by using the mechanical alloying and solid-state reaction methods, Te was substituted into Se sites within Cu2 Se as the formula Cu2 Se1− x Te x ( x = 0.1, 0.2, 0.25, and 0.3). The observed changes in structural phase, grain morphologies, and grain size were recorded by XRD and FE-SEM imaging with the appearance of the secondary phase of Cu2 Te, with a Te content of x = 0.25. The layered structure morphology was observed more clearly at the high Te content. The electrical conductivity was greatly increased with enriched Te content while the maximum Seebeck coefficient was obtained in the Cu2 Se0.75 Te0.25 sample. Accordingly, a power factor value of up to 9.84 μW cm −1 K −2 at 773 K was achieved. The appearance of a Cu2 Te phase with a Te content of 0.25 created a structural phase transition which results in a ZT value of 1.35 at 773 K in the Cu2 Se0.75 Te0.25 sample.